Sustaining Nigerian Culture in the 21st Century Via Literature: A Study of Chioma Njoku’s “Taboo in the Village” - CHIOMA WINNER ONYEAMA; ANN D. OGUAMANAM; IFEYINWA JULIANA UMEH (International Journal of Global Sustainable Research, 2025)
In the African context, issues pertaining to incest are of significant gravity and, if handled with levity is believed to have devastating repercussions for both the offenders and their families. Social change has adversely affected the perpetuation of norms, cultural practices, shared values and behavioral patterns that define a society. Reclaiming our values, traditions and societal norms amidst the challenges posed by globalization is of utmost importance. This paper adopting J.L. Austin (1962) speech acts presents a sociolinguistic examination of thirty-one excerpts randomly sampled from Chioma Njoku’s novel “Taboo in the Village”, which unveils the intricate relationship between customs and traditions with regards to incestuous sexual offence within a Nigerian cultural milieu. Through the lens of sociolinguistics, this research scrutinizes the linguistic choices within the text that addresses this sensitive subject of incest. Consequently, the study advocates for the re-establishment of African literature study within the General Studies curriculum, specifically in the "Communication in English" course (GST 111), as endorsed by the Nigerian University Commission in the Core Curriculum Minimum Academic Standard (CCMAS). Furthermore, it is imperative that parents and guardians impart knowledge to their wards regarding the traditions of their respective communities, utilizing methods such as story-telling or the reading of fictional literature, in order to avert the possibility of their engagement in immoral conduct